Consultas planteadas al ICAC - Fernández, Francisco Javier; González, Ángel (Revista de Contabilidad y Tributación. CEF, 2002)
BOICAC núm. 47, 09-2001. Consulta 4. BOICAC núm. 38, 06-1999. Consulta 7.